The role of life values in subjective well-being among Czech and Maltese university students - Alena Slezackova; Carmel Cefai; Eliska Cejkova; Stepanka Gassmann (Psihološka Obzorja, 2018)
In our cross-cultural comparative study, we aimed to explore the level of subjective well-being and hierarchy of life values among Czech and Maltese university students. The links between life values and cognitive and affective components of subjective well-being were also investigated. The research sample (N = 280, aged 18 to 30 years, M = 21.9 years, SD = 2.5) consisted of 165 Czech and 115 Maltese university students, who completed the Satisfaction with Life Scale, the Happiness Measure, and the Valued Living Questionnaire. The results showed that Czech and Maltese samples did not significantly differ in the levels of life satisfaction and happiness. Differences were revealed in the hierarchy of life values and in their relationship to subjective well-being in the two samples. Our study has shown that cultures might differ in the amount of importance they assign to various life values, and that cognitive and affective components of subjective well-being might be predicted by unique variables in different national samples.